(untitled) (Nigerian Journal of Physiological Sciences, 2022)
The present study was designed to investigate the effects of caffeine and adrenaline administration on memory and anxiety in male rats. Rats weighing about 140-200g were used for the study. They were divided into three groups (4 animals per group). Study groups 1; a,b,c,d were healthy rats administered normal saline, 5,10 and 15mg/kg bw caffeine intraperitoneally (i.p.), respectively for 6 weeks. Study groups 2; a,b,c,d administered normal saline, 0.1, 0.2 and 0.31mg/kg bw adrenaline (i.p.), respectively for 6 weeks. Study groups 3; a,b,c,d administered normal saline, 5mg/kg caffeine (i.p.) + 0.1mg/kg adrenaline (i.p.), 10mg/kg Caffeine (i.p.) + 0.2mg/kg Adrenaline (i.p.) and 15mg/kg Caffeine (i.p.) + 0.3mg/kg Adrenaline (i.p.) respectively for 6 weeks. The result showed no significant difference in spatial memory across all animals in study groups 1: b,c,d when compared to control (a). Study groups 2: (b, c) showed increase in spatial memory when compared to control (a). 2(d) showed a significant (p<0.05) decrease. Study groups 3: b, c, d showed no significant difference in spatial memory when compared to control (a). Study groups 1: b, c showed significant (p<0.05) reduction in duration for the short and long term memory test when compared to control. Study groups 2 showed reduction in duration for both the long and short term memory test when compared to control Study groups 3 no significant (p<0.05) difference in short and long term memory test across all animals in the group. It was also observed that adrenaline enhanced short and long term memory and only high dose of adrenaline distorted spatial memory. Study groups 1; (b,c) showed significant (p<0.05) increase in the number of entries to the open arm of the elevated plus maze when compared to control (a). Study groups 2; (b), showed significant (p<0.05) increase in the frequencies of entries to the closed arm of the elevated plus maze when compared to control (a). Study groups 2; (d), showed a significant (p<0.05) decrease in the frequency of entries to the open and closed arm when compared to control (a). The study revealed that co- administration of caffeine and adrenaline led to elevation of mood, increased activity and reduction of anxiety in Wistar rats. In addition, it was observed that only high dose of adrenaline increased anxiety. It was also observed that caffeine and adrenaline enhanced short and long term memory and only high dose of adrenaline distorted spatial memory.